Association of Autoantibodies against M2-Muscarinic Acetylcholine Receptor with Atrial Fibrosis in Atrial Fibrillation Patients. (4th February 2019) - Ma, Guiling; Wu, Xuejiao; Zeng, Lijun; Jin, Jiawei; Liu, Xingpeng; Zhang, Jianjun; Zhang, Lin
Abstract : Objectives . To investigate the association of serum autoantibodies against M2-muscarinic acetylcholine receptor (anti-M2-R) with atrial fibrosis in long-standing persistent atrial fibrillation (AF) patients. Methods . Twenty-four long-standing persistent AF patients, scheduled to undergo hybrid ablation surgery, were enrolled in the study. Twenty-six patients with sinus rhythm, scheduled to undergo coronary artery bypass grafting surgery, were enrolled into the non-AF group. We detected serum anti-M2-R levels. Left atrial appendages were subjected to histological and molecular biological assays. Patients in the AF group received follow-up for two years. Results . The AF group showed significantly higher serum anti-M2-R levels compared to the non-AF group (496.2 ± 232.5 vs. 86.3 ± 25.7 pmol/L, p < 0.001 ). The AF group exhibited severe fibrosis in the left atrial appendages, as indicated by increased collagen volume fraction (45.2 ± 4.7% vs. 27.6 ± 8.3%, p < 0.001 ), and higher levels of collagen I (0.52 ± 0.04 vs. 0.24 ± 0.06, p < 0.001 ) and collagen III (0.51 ± 0.07 vs. 0.36 ± 0.09, p < 0.001 ). TGF- β 1 and CTGF were also upregulated in the AF group. A positive correlation between serum anti-M2-R levels and fibrosis of the left atrial appendage and fibrogenic indexes was observed. Conclusions . Serum anti-M2-R levels are higher in AF patients and are associated with the severity of atrial fibrosis. In addition, serum anti-M2-R levels are positively correlated to TGF- β 1 and CTGF expression in the left atrial appendage.